Influence of Microwave and Conventional Annealing Processes in Improving an Electrodeposited Nickel Interlayer Characteristics - Hassan, A.; Noordin, M.; Izman, S.; Kurniawan, Denni (Springer New York LLC, 2016)
Nickel interlayer was coated on tungsten carbide substrate by electrodeposition process for the purpose of diamond deposition. Conventional and microwave annealing processes were used to improve the adhesion strength and modify the surface composition of the electroplated nickel interlayer. The conventional annealing was conducted in a high-temperature tube furnace at 1323.15 K (1050 °C) for 20 and 60 minutes annealing durations. The microwave annealing was carried out in 2.45 GHz microwave furnace at 1303.15 K (1030 °C) for the same annealing durations as the conventional process. The annealed specimens were characterized by electron microscopy, Energy dispersive X-ray spectroscopy, and X-ray diffraction technique. Adhesion of the annealed nickel interlayer was assessed by the scratch test. The results revealed significant changes in the nickel coating composition, adhesion, and appearance. The adhesion strength of nickel interlayer annealed for the longer duration of the two processes is similar. For shorter annealing duration, the microwave-annealed coating showed better adhesion. The surface composition of the nickel interlayer was modified by the diffusion of carbon and tungsten during the microwave and conventional annealing, respectively. The microwave annealing is a promising process for producing good quality treated nickel-coated tungsten carbide specimens.